A Communication Coding System for Use in High Conflict Interpersonal Relationships - Dunbar, Norah E.; Summary, Jennifer J.; Jackson, Felecia F. Jordan; Nassuna, Rita (Frontiers in Communication, 2022)
Conflict is a natural but uncomfortable part of all human relationships. Researchers and practitioners alike are interested in developing training and therapeutic methods for teaching couples and families healthy conflict management styles. However the research literature offers little for practitioners in the way of specific verbal and nonverbal “skills” they can teach to their clients and patients. In this paper, we examine the work of Dr. Steven Winer, educator and practitioner in Communication, with a focus on anger management and conflict resolution in interpersonal relationships. We review the research literature on interpersonal conflict and compare it to the advice offered through Dr. Winer’s workshops, which he developed through years of viewing over 4000 videotapes of communication behavior patterns exhibited by his clients during conflict role-play sessions.